Perbandingan Performansi Protokol Routing Epidemic dan Maxprop Berdasarkan Mobilitas Node pada Delay Tolerant Network - Andi Yudiko Leonardo Solin; Rakhmadhany Primananda; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The DTN architecture provides a solution for communication with long delay and intermittent connectivity. The moving node results in the large number of waiting time required by data packets to receive information from source to destination through many nodes. The movement of nodes that occur will produce such a patterned pattern movement and random movement. In sending messages DTN apply some routing protocols used in a different location and situation. DTN protocol in this research is routing Epidemic and Maxprop by doing DTN network simulation on The ONE Simulator to compare the performance of DTN protocol based on node mobility with the addition of node and message size. The results show that in the case of Delivery Probability routing Maxprop has better performance tendency than Epidemic routing with the highest Delivery Probability value on patterned movement 89% compared to 88% in Epidemic. On the random movement the best value of Delivery Probability produced is 41% compared to 35% in routing Epidemic. The Best value of Overhead Ratio routing Maxprop on patterned movement is 6,1379 compared to 7,9173 in Epidemic. On random movement the best of Overhead Ratio value is 4,0769 versus 3,7143 on Epidemic routing. The best Average Latency of routing Maxprop on patterned movement is 513,1642s compared to 574,1728s in Epidemic. In the random movement, routing Epidemic and Maxprop have the same Latency Average value is 1389.3500s